2021
DOI: 10.1109/tnsre.2021.3092140
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Functional Brain Network in MDD Based on Improved Empirical Mode Decomposition With Resting State EEG Data

Abstract: At present, most brain functional studies are based on traditional frequency bands to explore the abnormal functional connections and topological organization of patients with depression. However, they ignore the characteristic relationship of electroencephalogram (EEG) signals in the time domain. Therefore, this paper proposes a network decomposition model based on Improved Empirical Mode Decomposition (EMD), it is suitable for timefrequency analysis of brain functional network. On the one hand, it solves the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Although the Ho-BFN proposed in this study can be helpful in the diagnosis of patients with MDD, several limitations could be discussed. As in many previous studies ( Shao et al, 2021 ; Zhu et al, 2021 ), the first limitation relates to the small sample size. In the future, further validation of the reliability of our method with larger sample sizes (e.g., using other publicly available datasets) should be considered to avoid possible overfitting issues.…”
Section: Discussionmentioning
confidence: 99%
“…Although the Ho-BFN proposed in this study can be helpful in the diagnosis of patients with MDD, several limitations could be discussed. As in many previous studies ( Shao et al, 2021 ; Zhu et al, 2021 ), the first limitation relates to the small sample size. In the future, further validation of the reliability of our method with larger sample sizes (e.g., using other publicly available datasets) should be considered to avoid possible overfitting issues.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, research on MDD has focused on brain structure and function using morphological or neurobiological features. Functional magnetic resonance imaging (fMRI), magnetoencephalography (MEG), electroencephalography (EEG), and positron emission tomography (PET) are the common physiological methods employed in comparing people with MDD to healthy controls (HCs) (5). Researchers have found that patients with MDD have abnormal communication among the functional brain networks using functional connectivity (FC) of resting-state fMRI (R-fMRI), which detects synchronized and desynchronized spontaneous activity within anatomically diverse networks (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 20 ] extracted linear and nonlinear EEG features, selected features closely related to depression from different frequency bands using five feature selection algorithms, and then realized effective depression detection. Literature [ 21 – 23 ] has successively realized MDD detection based on BFN from different aspects such as graph theory analysis, minimum spanning tree, and improved empirical mode decomposition.…”
Section: Introductionmentioning
confidence: 99%